Do third age adults benefit equally in well-being from activity participation? The moderating effect of financial status - Nan Qin; Daniel W. L. Lai (PLoS ONE, 2025)
The relationship between activity participation and well-being has been well documented for third age adults. However, little has been known about how the financial status influences this relationship. This study aims to investigate the moderating effect of financial status on the association of activity level with subjective happiness and quality of life among third age adults. Systematic sampling was used to select a sample of 304 adults aged 50 and older from an active ageing institute in Hong Kong. Hierarchical regression analyses indicated that activity level was a salient predictor for subjective happiness and quality of life when controlling for socio-demographics. It was not salient anymore when its interaction term with financial status was added to the model. The interaction term significantly predicted quality of life but not subjective happiness. When the data were separated by financial status, activity level saliently predicted subjective happiness and quality of life for participants with good or very good financial statuses but not for those with poor or average statuses. The results suggested that financial status played a moderating role in the relationship between activity participation and well-being. Specifically, third age adults with limited financial resources need more welfare support to benefit from activity participation.